2022
DOI: 10.1182/bloodadvances.2021006405
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of von Willebrand factor with blood cells in flow models: a systematic review

Abstract: The presence of blood flow influences the interaction between von Willebrand factor (VWF) and blood cells, affecting characteristics of forming blood clots. The interactions between coagulation and inflammation have mainly been studied in thrombosis models, but it remains unclear whether these interactions might also play a role in reduced bleeding in patients with bleeding disorders. In this systematic review, we provide an overview of the literature investigating the interactions between VWF and blood cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 110 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…In this condition, endothelial-derived ADP may trigger platelet activation, following which receptors such as αIIbβ3 integrins [120], CD40L (CD154) and P-selectin become highly expressed on the surface of ECs [121]. These are important mediators in interactions with fibrinogen and other circulating cells in the blood [122]. As previously mentioned, vWf is released from the endothelial Weibel-Palade bodies into the bloodstream.…”
Section: Coagulant Damagementioning
confidence: 98%
See 1 more Smart Citation
“…In this condition, endothelial-derived ADP may trigger platelet activation, following which receptors such as αIIbβ3 integrins [120], CD40L (CD154) and P-selectin become highly expressed on the surface of ECs [121]. These are important mediators in interactions with fibrinogen and other circulating cells in the blood [122]. As previously mentioned, vWf is released from the endothelial Weibel-Palade bodies into the bloodstream.…”
Section: Coagulant Damagementioning
confidence: 98%
“…As previously mentioned, vWf is released from the endothelial Weibel-Palade bodies into the bloodstream. In vessels with lower shear stress and the presence of vWf, erythrocytes tend to aggregate, rolling on and adhering to ultralarge vWf multimer strands released from activated ECs [122]. Subsequently, platelets interact with the A1 domain of vWf, resulting in additional platelet binding and platelet activation [123].…”
Section: Coagulant Damagementioning
confidence: 99%
“…In a crucial study [ 103 ] predating the discovery of NETs [ 57 ], a distinct binding between the A1 domain of VWF and histones had been identified, elucidating the purpose of this interaction site on VWF. It has been observed that recombinant ADAMTS13 therapy not only clears VWF from endothelial surfaces, but also removes NETs [ 83 , 84 , 104 , 105 , 106 , 107 ] ( Figure 4 ).…”
Section: Interaction Of Nets With Ultra-large Vwf In Thromboinflammat...mentioning
confidence: 99%
“…Figure 4 demonstrates a clear interaction between VWF and and histones both bind to VWF, effectively anchoring NETs in place [100-10 study [103] predating the discovery of NETs [57], a distinct binding betwe main of VWF and histones had been identified, elucidating the purpose of th site on VWF. It has been observed that recombinant ADAMTS13 therapy n VWF from endothelial surfaces, but also removes NETs [83,84,[104][105][106][107] (Fig Histological examination of both animal and human thrombi reveals interwoven fibrin, NETs, and VWF localized in the solid matrix of thrombi. VWF stabilises the thrombus by acting as a bridge between the vessel wall and the NETs.…”
Section: The Role Of Vwf and Adamts13mentioning
confidence: 99%